A novel approach for tuberculosis diagnosis using exosomal DNA and droplet digital PCR. (July 2020) - Cho, S.M.; Shin, S.; Kim, Y.; Song, W.; Hong, S.G.; Jeong, S.H.; Kang, M.S.; Lee, K.A.
Abstract: Objectives: The rapid diagnosis of tuberculosis (TB) is important for patient treatment and infection control. Current molecular diagnostic techniques for TB have insufficient sensitivity to detect samples with low bacterial loads. The sensitivity of molecular testing depends on not only the performance of the assay technique but also the nucleic acid extraction method. Here, we present a novel approach using exosomal DNA (exoDNA) and droplet digital PCR (ddPCR) platforms to detect Mycobacterium tuberculosis DNA in clinical samples. Methods: The ddPCR platform targeting IS6110 was evaluated in parallel using total DNA and exoDNA. The clinical performance of ddPCR method was assessed with 190 respiratory samples from patients with suspected pulmonary TB. Results: Compared with mycobacterial culture, sensitivity and specificity of ddPCR were 61.5% (95% CI 44.6–76.6%) and 98.0% (95% CI 94.3–99.6%) using total DNA, and 76.9% (95% CI 60.7–88.9%) and 98.0% (95% CI 94.3–99.6%) using exoDNA, respectively. Among 15 culture-positive specimens with low concentrations of target molecules (2 99 positive droplets with exoDNA), only 53.3% (8/15), 46.7% (7/15), and 26.7% (4/15) of cases were detected using ddPCR with total DNA, real-time PCR with exoDNA, and real-time PCR with total DNA, respectively. Discussion: Our platform using ddPCR and exoDNA has the potential to provide sensitive and accurate methodology for TB diagnosis.